The Influence Of Marketing Mix On Consumer Satisfaction At Jeruk. In Teluk Betung - Claudio Christopher Valentino; Herry Goenawan Soedarsa (International Journal of Economics, Business and Innovation Research, 2024)
The purpose of this study is to ascertain how the marketing mix affects customer satisfaction in Teluk Betung. The target audience for this study is consumers in Jeruk.in Teluk Betung, and the sample size for this study is 50 individuals. employing multiple linear regression analysis as a method of analysis. According to the study's findings, the marketing mix as a whole had a confirmed and verifiable positive and considerable impact on Jeruk.in Teluk Betung's consumer happiness. It is intended that Jeruk.in Teluk Betung can increase customer satisfaction by using the study to maintain the stability of a suitable marketing mix for clients.